DIAGNOSIS AND TREATMENT OF ADHESIVE SMALL BOWEL OBSTRUCTION WITH USING LAPAROSCOPIC METHOD - Shonazarov Iskandar Shonazarovich; Adizov Faridun Ergashqul ugli (Research Focus International Scientific Journal, 2023)
Adhesive disease of the abdominal cavity, complicated by acute intestinal obstruction, is one of the most difficult diseases of the abdominal cavity in terms of treatment and diagnosis. The urgency of the problem is determined by the complexity of prevention and treatment of the studied complication, the widespread increase in surgical activity, the expansion of indications for performing operations of extended volume and combined interventions for diseases of the abdominal cavity and retroperitoneal space. Analysis of the literature shows that acute intestinal obstruction occupies one of the first places among urgent pathology of the abdominal cavity in terms of the frequency of complications and fatal outcomes. An increase in the number of patients, the severity and recurrent nature of the disease, difficulties in diagnosis, unsatisfactory immediate and long-term results of treatment of patients with adhesive small bowel obstruction, as well as a high percentage of disability determines the relevance of the chosen topic.